Hasidic commentary on the Torah - Wiskind-Elper, Ora 1960- (London Littman Library of Jewish Civilization in association with Liverpool University Press, 2018)
Introduction -- 1. Dimensions of Collective Self-Understanding. Beginnings ; Receiving, Revealing ; 'When Your Wellsprings Will Flow Forth' ; To Create New Worlds with Words ; 'They Made Their Souls Anew' ; To See and to be Seen ; 'Well said, Moses!' -- 2. Modes of Reading. Metaphors We Live By ; A Parable in Waiting ; Imagining the World ; The Essence of Being Human ; Bread-Eaters and Dreamers ; Know Me in Translation ; Conclusions So Far ; How to Teach, How to Learn ; To Know or Not to Know ; Finding the Words ; The Secret of Exile ; The Secret of Redemption ; Summing Up -- 3. Responses to a Shifting Landscape. The Space in the Middle ; 'For the Times They are A-Changin' ; Reason for Hope ; The Inward Turn ; Modernity and Its Discontents ; 'God is in the Detail' ; Prophets of the Past, Prophets of the Future ; Deep Blue Sky and Yellow Stars ; Song of Dust and Ashes ; Postscript.
"Hasidism, a movement of religious awakening and social reform, originated in the mid-eighteenth century. After two and a half centuries of crisis, upheaval, and renewal, it remains a vibrant way of life and a compelling aspect of Jewish experience. This book explores the profound intellectual and religious issues that the hasidic masters raised in their Torah commentary, and brings to the fore the living qualities of their sermons (derashot). Ora Wiskind-Elper addresses a spectrum of topics: creation, revelation, and redemption; hermeneutics, epistemology, psychology, Romanticism, poetry and poetics, art history, Hebrew fiction, cultural history, and tropes of Jewish suffering and hope. Fully engaged in the texts and their spirituality, she brings them to bear on postmodernist challenges to traditional spiritual and religious sensibilities. This is a comprehensive study, unique in pedagogy, clarity, and originality. It uses the full range of critical scholarship on hasidism as a social and ideological movement. At the same time, it maintains a strong focus on hasidic Torah commentary as a conveyor of theology and value. Each of its chapters presents a fundamentally new approach. Wiskind-Elper's translations are in themselves an innovative moment in the tradition and spiritual history of the passages she offers"--front flap
Includes bibliographical references (pages 193-209) and index
Keywords: Bible -- Commentaries; Hasidism